Leontopodium andersonii (Asteraceae), a new genus record to Thailand - Munsuk, Wanniga; Suksathan, Piyakaset; Pornpongrungrueng, Pimwadee (Thai Forest Bulletin (Botany), 2020)
Leontopodium andersonii is here for the first time recorded for Thailand, and is also the first record of the genus Leontopodium (Asteraceae) in Thailand. A description and an illustration are provided.